2012
DOI: 10.1111/j.1466-7657.2012.01017.x
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to support breastfeeding: a review

Abstract: Mothers benefit from strategies that encourage breastfeeding, with guidance that supports their self-efficacy and feelings of being capable and empowered, and is tailored to their individual needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 40 publications
1
20
1
3
Order By: Relevance
“…A study among Indigenous women with GDM in the United States reported a high ‘perception of risk’ coupled with low levels of self‐efficacy for preventing cardio‐metabolic disease, 27,28 a combination associated with avoidance behaviour 29 . This suggests recommendations to include confidence‐building (‘strengths‐based’) strategies in breastfeeding support 30 may be particularly important for Indigenous women with GDM. Women with GDM experience delayed lactogenesis (onset of lactation) 31 and increased risks of caesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…A study among Indigenous women with GDM in the United States reported a high ‘perception of risk’ coupled with low levels of self‐efficacy for preventing cardio‐metabolic disease, 27,28 a combination associated with avoidance behaviour 29 . This suggests recommendations to include confidence‐building (‘strengths‐based’) strategies in breastfeeding support 30 may be particularly important for Indigenous women with GDM. Women with GDM experience delayed lactogenesis (onset of lactation) 31 and increased risks of caesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…Women with gestational diabetes, and their infants, are more likely to experience interventions and complications during pregnancy and birth which may inhibit breastfeeding, such as caesarean section and neonatal hypoglycaemia, and therefore are likely to require additional support postpartum. Further, Indigenous women are more likely to be categorised as having as having 'low socio-economic status', which is associated with a lower confidence with breastfeeding [102] and postpartum weight loss [103], suggesting positive encouragement and support may be helpful.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that breastfeeding promotion programs delivered via the Internet significantly improved knowledge, positive beliefs, and breastfeeding intentions than offline, healthcare provider-based interventions (O'Connor, Brown, & Lewin, 2011;Pate, 2009). Despite the increasing interest in Internet-based breastfeeding promotion, education, and programs, the most recent literature review on strategies to support breastfeeding (see : Demirtas, 2012) heavily focuses on face-to-face communication between mothers and family members or health professionals. Relatively little is known about communication centered on probreastfeeding women and their UGC via social media channels.…”
Section: Theoretical Frameworkmentioning
confidence: 99%